2009
DOI: 10.1002/rcm.4189
|View full text |Cite
|
Sign up to set email alerts
|

A numerical evaluation of chamber methodologies used in measuring the δ13C of soil respiration

Abstract: Measurement of the delta(13)C value of soil-respired CO(2) (delta(r)) has become a commonplace method through which ecosystem function and C dynamics can be better understood. Despite its proven utility there is currently no consensus on the most robust method with which to measure delta(r). Static and dynamic chamber systems are both commonly used for this purpose; however, the literature on these methods provides evidence suggesting that measurements of delta(r) made with these chamber systems are neither re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…8 ‰ more positive than those in Experiment A. We suppose this is due to isotopic fractionation in the transient-state diffusion of respired CO 2 through the soil to the microcosm chambers, as discussed by Nickerson andRisk (2009) andOhlsson (2010). In systems using purged chambers, such as ours, this can produce a positive δ 13 C bias of up to 15 ‰ (Nickerson and Risk, 2009).…”
Section: Isotope Fractionation During δ 13 C Measurementsmentioning
confidence: 69%
See 3 more Smart Citations
“…8 ‰ more positive than those in Experiment A. We suppose this is due to isotopic fractionation in the transient-state diffusion of respired CO 2 through the soil to the microcosm chambers, as discussed by Nickerson andRisk (2009) andOhlsson (2010). In systems using purged chambers, such as ours, this can produce a positive δ 13 C bias of up to 15 ‰ (Nickerson and Risk, 2009).…”
Section: Isotope Fractionation During δ 13 C Measurementsmentioning
confidence: 69%
“…The values measured in the control soils in Experiment B were significantly less negative than those in the control soils in Experiment A. Following Nickerson and Risk (2009) and Ohlsson (2010), we suppose this is due to isotopic fractionation in transient-state diffusion of respired CO 2 through the soil to the purged microcosm chambers, which is expected to be greater in Experiment B for reasons discussed in Appendix A. In calculations given in Appendix A, we show that the apparent error in δ 13 C values will cause the size of the priming effect to be under-estimated, but the trends across the treatments and over time are unchanged.…”
Section: Isotope Fractionation Effectsmentioning
confidence: 73%
See 2 more Smart Citations
“…Nickerson and Risk, [66] using a 3D soil-atmosphere-chamber model, recently confirmed these observations, and suggested that this approach is inherently biased due to chamber-to-soil feedbacks. These feedbacks arise from non-steady-state conditions, with the build up of CO 2 in the chamber influencing the diffusion of soil CO 2 and its isotopologues, which would be an issue for all chamber systems, to a greater or lesser extent, [66] with dynamic chambers (see later) offering possibly the least disturbance.…”
mentioning
confidence: 78%